Pengaruh Variasi Tebal Orifice dan Bilangan Reynolds (Re) terhadap Penurunan Tekanan (Pressure Drop) pada Entrance Region - Amnur Akhyan; Fadhli Fadhli (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2023)
Orifice is a device that is placed in a pipe flow to inhibit the flow of fluid and cause a pressure drop. The measurement of the flow rate (flow rate) is obtained from the difference in pressure due to the pressure drop. In this study, it analyzed the influence of differences in plate orifice thickness variations used ranging from 2 mm to 4 mm thick with variations in increments every 0.5 mm with an orifice center hole diameter of 1.5 cm. Orifice placement is placed in an area whose speed profile is still changing or called the entrance region with a pipe diameter used 2.54 cm (1 Inch) diameter in the pipe. Then along the entrance area are paired 12 piezometer points along 75 cm with a position of laying 6 piezometer points before the orifice valve and 6 piezometer points after the orifice valve and in this experiment set the Re value to 3 Variations of Re, namely Re 1: 9784.5; Re2: 14647.5; Re 3: 19510.45 and this experiment was carried out at a temperature of 27 °C. In this study, the results were obtained for the highest irrecoverable pressure drop value located in the flow discharge with Re 19510.45 and at the thickness of the plate orifice 4 mm with an irrecoverable pressure drop value of 3033.01 Pa and while for the lowest irrecoverable pressure drop value, it was located in the flow discharge with a value of Re 9784.5 at an orifice plate thickness of 2 mm with an irrecoverable pressure drop value of 548.26 Pa. The highest discharge of coefficient (Cd) value lies in the flow discharge with a value of Re 14647.5 at the plate orifice thickness of 3.5 with a Cd value of 0.718 and while for the lowest discharge of coefficient (Cd) value lies in the flow discharge with Re 14647.5 with an orifice plate thickness of 2 mm with a Cd value of 0.609.